The pursuit of sustainable leadership : becoming a successful strategic leader through principles, perspectives, and professional development - Rainey, David L. (Emerald Publishing Limited : Information Age Pub., 2013)
The Pursuit of Sustainable Leadership: Sustainable Leadership (SL) encompasses the broad roles and responsibilities of leaders that cut across the whole organization and the entire extended enterprise from horizon to horizon. The underpinnings of SL require strategic leaders and professionals to play leading roles in dealing with critical issues affecting business and people. This including resolving the related problems and challenges and participating in the development and deployment of sustainable solutions based on the full spectrum of needs and expectations of society, market spaces, and business environment. SL necessitates openness, inclusiveness, innovativeness, and fair mindedness. It requires strategic leaders to create an extraordinary vision and to fulfill their missions to develop, support, and promote the extended enterprises and the market spaces served by their businesses.Sustainable strategic leaders ensure that their organizations and enterprises are fully capable and responsive to external dimensions and market spaces and have the potential to be successful. They serve and support markets, customers, and stakeholders and provide them with solutions and successful outcomes. In addition, strategic leaders fulfill their broad responsibilities to society through positive actions to improve the social and economic fabric of the human world and to mitigate the negative impacts across all of the social, economic, and environmental aspects.The Pursuit of Sustainable Leadership (PSL) involves the ongoing learning and development of business leaders and students to become true strategic leaders who have the proper principles, philosophies, values, capabilities and perspectives for achieving sustainable success. True leaders are dedicated to their endeavors and never stop making transitions and transformations to higher levels of sophistication. The PSL is based on a learning the foundations of leadership, having the right principles, developing personal philosophies, using broad perspectives, adapting openness and honesty, engaging in continuous learning, embracing lifelong personal and professional development, and being a sustainable leader. The key to success involves acquiring new knowledge, seeking profound experiences, expanding one's understanding of realities and possibilities, and developing positive mindset through demanding roles and responsibilities, interactive engagements and profound learning.